New Data concerning the Epidemiology of Hepatitis B Virus Infection in Greece - Konstantinos D. Pantazis; Ioannis S. Elefsiniotis; Hero Brokalaki (Gastroenterology Research and Practice)
There is an obvious, significant, and diachronic reduction of the prevalence of HBV infection in Greece, concerning the general population as well as some traditionally high-risk groups, mainly as a result of constant informing and the widespread initiation of preventive and prophylactic measures, as well as the improvement of health care services. Nevertheless, there are special groups and populations (economical refugees, religious minorities, HIV-positive patients, abroad pregnant women, prostitutes, etc.) who represent sacs of high HBV endemicity and need epidemiological supervision and intervention, in order to limit the spread of the infection and to further improve the existing epidemiological data.